2012
DOI: 10.1093/hmg/dds324
|View full text |Cite
|
Sign up to set email alerts
|

Impaired proteolysis underlies autophagic dysfunction in Niemann–Pick type C disease

Abstract: Niemann-Pick type C disease (NPC) is a childhood onset neurodegenerative disorder arising from lipid-trafficking defects caused by mutations in the NPC1 or NPC2 gene. Marked accumulation of autophagosomes is a prominent feature of NPC cells, yet a detailed understanding of the disease-associated alterations in autophagy and their role in pathogenesis has been lacking. Prior studies have shown that lipid storage in NPC disease induces autophagy. Here, we additionally show that the clearance of autophagosomes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
121
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(135 citation statements)
references
References 68 publications
12
121
2
Order By: Relevance
“…27 Using human embryonic stem cell-derived neurons, it was shown that both induction of basal autophagy and impaired autophagic flux concomitantly occur with NPC1 knockdown and that this significantly compromises mitochondrial clearance. 26 Remarkably, these changes were partially reversible through the application of the autophagy inhibitor 3-methyladenine, which reduces autophagosome formation and, by treatment with cyclodextrin, a compound capable of mobilizing cholesterol from the lysosomal compartment.…”
Section: Reviewmentioning
confidence: 99%
“…27 Using human embryonic stem cell-derived neurons, it was shown that both induction of basal autophagy and impaired autophagic flux concomitantly occur with NPC1 knockdown and that this significantly compromises mitochondrial clearance. 26 Remarkably, these changes were partially reversible through the application of the autophagy inhibitor 3-methyladenine, which reduces autophagosome formation and, by treatment with cyclodextrin, a compound capable of mobilizing cholesterol from the lysosomal compartment.…”
Section: Reviewmentioning
confidence: 99%
“…It has been proposed that altered lipid content (i.e., high cholesterol or ganglioside levels) may contribute to autophagy impairment. [20][21][22][23][24] On the other hand, the lipid that most significantly accumulates in neurons from ASMko mice is SM. 10 Hence, we directly tested whether SM accumulation was responsible for the autophagosome-lysosome alterations observed in the ASMko mice brain.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, ASMko mice brains show cholesterol deposits 29,30 and the accumulation of this lipid impairs lysosomal function in different LSDs. 21,22,24 To test cholesterol involvement, NPA fibroblasts were incubated with methyl-b-cyclodextrin, which sequesters this lipid without affecting SM. 31 Treatment for 24 h with 0.3 mM methyl-b-cyclodextrin had no effect on LC3-II levels ( Figure 5c) despite its efficiency in reducing cholesterol levels by 16% (Figure 5d), similar to the 15% SM reduction promoted by FB1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations